Pemanfaatan Kriptografi dalam Mewujudkan Keamanan Informasi pada E-Voting di Kota Medan dengan Menggunakan Algoritma AES - Mhd. Aria Agung Widodo; Myra Thasandra; Septia Ona Sutra; Adnan Buyung Nasution; Ali Ikhwan (Departement of Mathematics Education, 2023)
Electronic “voting or e-voting is a form of voting that is usually used for elections or polls using electronic media. There is a shift in the use of media that used to be conventional and in the current technological era, there are many various media used for opinion polls, including social media/internet. In the next few years, through the USO (Universal Service Obligation) program, the government will provide voice and data communication access facilities to reach all villages in the country so that e-Voting is increasingly likely to be implemented. The E-Voting system is one way to help solve this problem. The security of the E-Voting system is guaranteed and in accordance with current technological developments. The system can be combined with various cryptographic algorithms to increase security, one of which is the AES cryptographic algorithm. Cryptography can be used to answer questions related to information security in the form of confidentiality, non-denial, and authentication. In this journal, it will be explained how to use cryptography in realizing information security in e-Voting in Medan City Using the AES Algorithm Method”.